The problem of etiology of children hyperactivity - Chomentauskienė, R. (Psichologija, 1987)
The most frequently proposed etiology of hyperactivity is organic brain damage or neurologic dysfunction. The experimental studies conducted in the past decade revealed that organic factors play certain role in some cases, though they occur only in a small portion of hyperactive population. The studies also showed the importance of psychogenic factors in hyperactivity - of parenting styles, interaction patterns and learning, - which till lately have been ignored. The existence of a variety of etiological agents of hyperactivity poses the necessity of distinguishing several etiological subgroups. However, only limited experimental data account for psychogenic hyperactivity. The current studies mostly analyze the role of psychological factors in behavioural terms, which is not enough for pointing out the mechanism of their influence. The psychological mechanism of hyperactivity can only be identified by studying the subjective logics of child behaviour, his subjective interpretation of the surrounding world - not only external determinants of hyperactive behaviour, as it has been commonly done.